Immunotherapy approaches for the treatment of diffuse midline gliomas. (31st December 2022) - Bernstock, Joshua D.; Hoffman, Samantha E.; Kappel, Ari D.; Valdes, Pablo A.; Essayed, Walid Ibn; Klinger, Neil V.; Kang, Kyung-Don; Totsch, Stacie K.; Olsen, Hannah E.; Schlappi, Charles W.; Filipski, Katharina; Gessler, Florian A.; et al.
ABSTRACT: Diffuse midline gliomas (DMG) are a highly aggressive and universally fatal subgroup of pediatric tumors responsible for the majority of childhood brain tumor deaths. Median overall survival is less than 12 months with a 90% mortality rate at 2 years from diagnosis. Research into the underlying tumor biology and numerous clinical trials have done little to change the invariably poor prognosis. Continued development of novel, efficacious therapeutic options for DMGs remains a critically important area of active investigation. Given that DMGs are not amenable to surgical resection, have only limited response to radiation, and are refractory to traditional chemotherapy, immunotherapy has emerged as a promising alternative treatment modality. This review summarizes the various immunotherapy-based treatments for DMG as well as their specific limitations. We explore the use of cell-based therapies, oncolytic virotherapy or immunovirotherapy, immune checkpoint inhibition, and immunomodulatory vaccination strategies, and highlight the recent clinical success of anti-GD2 CAR-T therapy in diffuse intrinsic pontine glioma (DIPG) patients. Finally, we address the challenges faced in translating preclinical and early phase clinical trial data into effective standardized treatment for DMG patients.